Quartz modification by Zn ion implantation and swift Xe ion irradiation - Privezentsev, Vladimir; Kulikauskas, Vaclav; Didyk, Alexander; Skuratov, Vladimir; Steinman, Edward; Tereshchenko, Alexey; Kolesnikov, Nikolay; Trifonov, Alexey; Sakharov, Oleg; Ksenich, Sergey (Physica status solidi. C, 2017)
The quartz slides were implanted by 64Zn+ ions with dose of 5 × 1016/cm2 and energy of 100 keV. After implantation, the amorphous metallic Zn nanoparticles with an average radius of 3.5 nm were created. The sample surface becomes nonuniform, its roughness is increased and its values rise up to 6 nm compared to virgin state, and the roughness maximum is at a value of about 0.8 nm. The surface is made up of valleys and hillocks which have a round shape with an average diameter about 200 nm. At the center of these hillocks are pores with a depth up to 6 nm and a diameter of about 20 nm. After implantation in UV‐vis diapason, the optical transmission decreases while PL peak (apparently due to oxygen deficient centers) at wavelength of 400 nm increases. Then the samples were subjected to swift Xe ion irradiation with the fluences of 1 × 1012–7.5 × 1014/cm2 and energy of 167 MeV. After Xe irradiation, the sample surface roughness shat down to values of 0.5 nm and the roughness maximum is at a value of about 0.1 nm. Optical transmission in UV‐vis diapason increases. The PL peak at wavelength of 400 nm is decreased while a PL peak at wavelength of 660 nm is raised. This peak is presumably due to non‐bridging oxygen hole centers or/and NPs with structure Si(core)/SiO2(shell). HRTEM image of Zn‐implanted quartz subsurface layer. One can see the Zn amorphous nanoparticles, which confirms the electron diffraction pattern (insert).